Historiography of the Mission of A.F. Negri that Has Been Sent by the Russian Empire to the Emirate of Bukhara - Hamraev S. A. (Researchparks Publishing, 2023)
This article is devoted to the historiography of the mission of A.F. Negri, who was sent to Bukhara as the ambassador of the Russian Empire. The article studies the tasks and purpose of this mission. The study of the history of this mission, its significance in the history of interaction between Bukhara and Russia was analyzed with the use of various approaches put forward by researchers in the process of its disclosure. In addition, in the course of the research, various points of view were presented on the results of the mission of A.F. Negri, more precisely, his diplomatic failure, which was represented with the help of primary sources